DAMPAK TINDAK KEKERASAN TERHADAP PEREMPUAN DAN ANAK SERTA SOLUSINYA - John Dirk Pasalbessy (Faculty of Law, Universitas Pattimura, 2010)
Violence is not just an individual problem or a national problem, but is already a global problem, even transnational. In the context of protection of human rights, as human beings, women and children also have the same rights. Efforts to prevent or cope with a variety of behaviors and violence experienced by women and children already have received serious attention and treatment. Therefore, the approach in handling these issues must be integrated (integrated), where in addition to the legal approach should also consider non-legal approach which is precisely the cause of violence.